2014
DOI: 10.14356/kona.2014006
|View full text |Cite
|
Sign up to set email alerts
|

Nanophosphor Coatings: Technology and Applications, Opportunities and Challenges

Abstract: The particle size of conventional commercial phosphor powders used in lighting and displays is in the range from several micrometers to tens of micrometers and it is known that submicrometer-sized phosphors can facilitate a decrease in their consumption and improved resolution of phosphor screens. When the particle size becomes comparable to wavelengths of light, the optical properties of phosphor powders undergo remarkable qualitative changes so that the luminescence performance of nanophosphor screens, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 228 publications
0
24
0
Order By: Relevance
“…Therefore, even the smallest of our particles do not give evidence that quantum confinement could improve luminescence performance. In contrast, studies have shown that the large surface area of nanoparticles host recombination centers and have adsorbates like water which quench luminescence [4]. The proposed effect of multiphonon emission competing with down conversion processes due to increased surface areas external and internal to the particles explains the decrease in luminescence as the particle size decreases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, even the smallest of our particles do not give evidence that quantum confinement could improve luminescence performance. In contrast, studies have shown that the large surface area of nanoparticles host recombination centers and have adsorbates like water which quench luminescence [4]. The proposed effect of multiphonon emission competing with down conversion processes due to increased surface areas external and internal to the particles explains the decrease in luminescence as the particle size decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In the display technology field, smaller particles are expected to improve resolution by combining the field emission of electrons with the cathodoluminescence of the particles [4,5,6,7,8,9,10]. For particles less than 10 nm in diameter, the possibility of exploiting quantum confinement effects with their respective changes in electron transitions and spectral details [2,11,12] have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations